Optimization and Treatment Characteristics for Green Synthesis of NiO Nanomaterials from White Broccoli (Brotrytis Cauliflower) Flower Extract with Varying pH, Temperature, and Stirring Speed - Nisah, Khairun; Hamdan, Abd Mujahid; Lubis, Syafrina Sari; Aini, Zahratul; Athika, Yawmil; Febrilia, Dea (Trends in Sciences, 2024)
This research aims to explore the effect of pH, temperature, and stirring speed on the characteristics of NiO nanomaterials synthesized using the green synthesis method from white broccoli flower extract (Brassica oleracea var. botrytis). Varying synthesis conditions were tested to determine the optimal conditions that produce nanoparticles with the desired size, distribution, and stability. Characterization was carried out using SEM-EDX, XRD, and TEM to observe the morphology, element composition, and crystal structure of the nanoparticles. The research results show that pH 11, temperature 60 °C, and stirring speed 750 rpm are optimal conditions for the synthesis of NiO nanoparticles with homogeneous size and distribution and good stability. HIGHLIGHTS Developed an eco-friendly synthesis route for NiO nanomaterials using white broccoli (Brotrytis cauliflower) flower extract. Studied the effects of varying pH, temperature, and stirring speed on the synthesis process. Performed detailed structural, morphological, and chemical analyses of the synthesized NiO nanomaterials. Determined the best synthesis conditions for producing high-quality NiO nanomaterials. Promoted a sustainable and cost-effective method for nanomaterial synthesis, aligning with green chemistry principles. GRAPHICAL ABSTRACT